Determination of illuminance level using ANN model - ATİŞ, SELÇUK; TOPUZ, VEDAT (Springer Verlag, 2007)
In this study, an illuminance determining method, using an artificial neural network (ANN) model, has been designed. The model was realized as an alternative to existing simulation programs to determine the illuminance of a working place. In the model, maintenance factor (MF), working plane (WP), suspension height (SH) of luminaries were selected as input parameters, average illuminance (Eav), minimum illuminance (Emin) and maximum illuminance (Emax) of working plane were selected as output parameters that are the effective parameters in establishment and maintenance of luminance. Comparison between the real time measurements, illuminance simulation program (ISP) and ANN model results has shown that designed ANN model is satisfied. © Springer-Verlag Berlin Heidelberg 2007.
Keywords: ANN model; Illuminance level